"The analysis on the issue of marital rape" / Hana Sakina Abdullah Sani...[et al.] - Abdullah Sani, Hana Sakina; Hisham, Hazila Natasha; Abdullah, Muhammad Ammar Hafiz; Syed Lan Osla, Sharifah Eliza (2006)
The issue of Marital Rape has been debated throughout the world among the feminist organizations. Since its recognition in some countries such as United States of America, Canada and Korea, Malaysia has also been exposed to the issue on Marital Rape. However, due to some circumstances, the law on Marital Rape faces some difficulties in terms implementation of the said law in Malaysia. The purpose of conducting this research is to analyze issue of marital rape throughout the world. In addition, whether the law of marital rape can be introduce in our country. Although there is no specific law in Malaysia on this issue, we cannot disregard the severity of this matter. This is due to the fact that around the world more and more countries have recognized marital rape as law. In order to produce this research, various sources will be referred to. These sources include legal materials such as statutes, case law and articles. Interviews have also been conducted with the legal academician of UiTM. It is hope that this research will give some wider perspective on the issue of marital rape in Malaysia.